Comparative Analysis of Cross-Platform Frameworks. - GAVILÁNEZ ALVAREZ, OSCAR DANILO; PUENTE RIOFRÍO, MARIANA ISABEL; MEJÍA CABEZAS, NORA TAHIRÍ; GAVILÁNEZ ALVAREZ, IRAIDA MARITZA; VARGAS ÑAUÑAY, ERICK JOEL; CHANGO VELA, KEVIN ARIEL; CARDENAS CARDENAS, LUIS ANGEL (Journal of Namibian Studies)
The use of frameworks for cross-platform development, whether native or hybrid, is a fundamental part of the field of programming, facilitating in one way or another to software developers to save time, reduce compilation errors, and optimize resources, among other features that denote some advantage between one tool and another. For this reason, it was decided to perform a comparative analysis between the cross-platform application development frameworks Flutter, React Native, Ionic, and Xamarin, using relevant features of each tool as parameters. For this purpose, research was conducted through a literature review of research articles, theses, and books obtained using the Google Scholar search engine, and consequently, parameters were determined that allowed comparing the mentioned frameworks. As a case study, a simple web page was developed in the Flutter framework with the help of the Visual Studio Code environment, to experiment with the characteristics of the mentioned framework directly and briefly. It is concluded that the frameworks for multiplatform development are useful tools that optimize time and maintenance by not requiring writing code to create a computer application on different platforms, benefiting developers and companies focused on software development.